A c-axis oriented SnSb2Te4 thermoelectric film and its preparation method

The preparation of c-axis-oriented growth of SnSb2Te4 thermoelectric films through pulsed laser deposition technology has solved the shortcomings in the existing technology in the research on two-dimensional film materials, and achieved high-quality and uniform film preparation, with good thermoelectric properties and device application prospects.

CN116356271BActive Publication Date: 2025-03-11香河汇文节能科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310163584.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-03-11
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The prior art mainly focuses on the research of three-dimensional bulk SnSb2Te4 thermoelectric materials, and lacks in-depth research on two-dimensional film materials, especially the research on preferred orientation films, which limits the integrated application of thermoelectric film devices.

Method used

Pulse laser deposition technology is used to prepare a c-axis-oriented thermoelectric film. By regulating substrate temperature, deposition pressure strength, deposition time, laser frequency and changing substrate material, the surface morphology, optimal orientation, crystallization mass, grain size and growth rate of the film are controlled.

Benefits of technology

It has achieved high-quality, uniform composition and easy-to-control SnSb2Te4 thermoelectric film preparation, with good thermoelectric performance and device application prospects, breaking through the limitations of three-dimensional bulk materials, and promoting the integrated application of thermoelectric film devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116356271B_ABST
    Figure CN116356271B_ABST
Patent Text Reader

Abstract

The present invention provides a c-axis oriented growth SnSb 2 Te 4 Thermoelectric film and its preparation method. The present invention adopts spark plasma sintering technology to prepare SnSb 2 Te 4 Polycrystalline target, growing SnSb on single crystal substrate using pulsed laser deposition technology 2 Te 4 Thin film, by adjusting the substrate temperature, argon pressure, laser energy density and other parameters, SnSb with good preferential orientation and high crystal quality is deposited on the single crystal substrate 2 Te 4 The SnSb film prepared by the method of the present invention 2 Te 4 The film has good thermoelectric properties and has broad application prospects in the fields of thermoelectric thin film devices and micro-area integrated electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermoelectric thin film materials, in particular to a SnSb2Te4 thermoelectric thin film grown in a c-axis orientation and a preparation method thereof. Background Art

[0002] With the development of the global economy, energy shortages and environmental pollution caused by the use of fossil energy have become increasingly prominent, and new clean energy conversion technologies are urgently needed. Thermoelectric materials and corresponding thermoelectric conversion technologies have broad application prospects in the fields of industrial waste heat power generation, automobile exhaust waste heat power generation, micro-mobile temperature difference power supplies, semiconductor refrigeration, etc. because they can realize the mutual conversion of heat energy and electrical energy through the Seebeck effect and the Peltier effect. The performance of thermoelectric materials is often measured by the dimensionless thermoelectric figure of merit ZT, which is defined as ZT = (S 2 σ / κ)T. Where S is the Seebeck coefficient of the material, σ is the electrical conductivity of the material, κ is the thermal conductivity of the material, and T is the absolute temperature. Among them, the electrical performance parameter S 2 σ is called the power factor. An ideal thermoelectric material should have a high power factor and a small thermal conductivity.

[0003] Ternary metal chalcogenide SnSb2Te4 (abbreviated as SST) is a layered material (trigonal structure, space group Lattice constant ), because of its high electrical conductivity σ and low thermal conductivity κ, it has potential application prospects in the field of thermoelectrics. At present, the research on the thermoelectric properties of SnSb2Te4 at home and abroad is almost entirely focused on three-dimensional bulk materials, and there is very little research on two-dimensional thin film materials. There has been no relevant research report on preferentially oriented thin films. Compared with three-dimensional bulk materials, two-dimensional thin film materials are easier to realize the integration of thermoelectric devices, and have irreplaceable advantages over bulk materials in the field of micro-area thermoelectric power generation and refrigeration. Summary of the invention

[0004] The purpose of the present invention is to provide a c-axis oriented SnSb2Te4 thermoelectric film and a preparation method thereof, so as to provide a SnSb2Te4 thermoelectric film preparation method having the advantages of high crystal quality, uniform composition, easy control, simple process, etc.

[0005] The present invention is achieved in that:

[0006] A method for preparing a SnSb2Te4 thermoelectric thin film grown in a c-axis orientation comprises the following steps:

[0007] (a) Preparation of target material: ① Mix Sn (99.999%), Sb (99.999%), and Te (99.999%) powders in a calculated ratio, and the molar stoichiometric ratio is Sn:Sb:Te=1:2:4; ② Place the uniformly mixed powders in a quartz tube and seal the tube in vacuum; ③ Place the vacuum-sealed quartz tube in a muffle furnace for melt sintering to form an ingot; ④ Crush and grind the sintered ingot into powder; ⑤ Sinter and press the powder obtained in step ④ using a spark plasma sintering technique to obtain a SnSb2Te4 polycrystalline target material.

[0008] (b) Cleaning the substrate: Use ultrasonic cleaning method to remove impurities such as grease on the surface of the substrate.

[0009] (c) Target placement: The SnSb2Te4 target is placed on the target holder of the epitaxial chamber of the pulsed laser deposition equipment.

[0010] (d) Placing the substrate: Use silver glue to glue the cleaned substrate to the center of the sample holder and place it into the heating table of the epitaxial chamber.

[0011] (e) Vacuuming: The back of the epitaxial chamber is vacuumed to less than or equal to 4×10 -4 Pa.

[0012] (f) Substrate heating: Run the heating program to heat the substrate at a rate of 10°C / min until the substrate temperature reaches the set temperature.

[0013] (g) Adjusting the pressure: After the substrate temperature reaches the set temperature, high-purity argon gas (99.999%) is filled into the epitaxial chamber. By adjusting the size of the filling and exhaust valves, the dynamic balance pressure of the argon gas is maintained at the set pressure and stabilized.

[0014] (h) Thin film deposition: The SnSb2Te4 target is bombarded with a pulsed laser for surface pre-sputtering to remove impurities on the target surface. After 5 to 10 minutes, the baffle shielding the substrate is removed and a SnSb2Te4 thin film is deposited on the single crystal substrate.

[0015] (i) Cooling: After sputtering, the material is naturally cooled to room temperature in a vacuum.

[0016] (j) Taking samples: After filling the epitaxial chamber with gas, take out the obtained SnSb2Te4 film.

[0017] Furthermore, in step (a), the sintering temperature of the powder in the quartz tube in the muffle furnace is set to 1150°C.

[0018] Furthermore, in step ⑤ of step (a), the powder is sintered under a spark plasma sintering process at a pressure of 50 MPa, a temperature of 500° C., and a sintering time of 7 min.

[0019] Furthermore, in step (b), the substrate is a single crystal substrate such as lanthanum aluminate (chemical formula: LaAlO3, abbreviated: LAO), strontium titanate (chemical formula: SrTiO3, abbreviated: STO), silicon wafer (chemical formula: Si), strontium tantalum aluminate (chemical formula: SrLaAlO4), magnesium oxide (chemical formula: MgO) or sapphire (chemical formula: Al2O3), with a crystal orientation tolerance of ±0.5°, a size of 10 mm×2.5 mm, and a thickness of 0.5 mm.

[0020] Furthermore, in the step (b), the substrate is cleaned by placing the substrate in acetone, anhydrous ethanol and deionized water in sequence and ultrasonically cleaning them for 10 minutes respectively.

[0021] Furthermore, in steps (c) and (d), the distance between the SnSb2Te4 target and the single crystal substrate is 50 mm.

[0022] Furthermore, in step (f), the temperature of the substrate is raised to 250°C to 300°C.

[0023] Furthermore, in step (g), the argon pressure in dynamic equilibrium is 0.1 Pa.

[0024] Furthermore, in step (h), the pulse laser is a XeCl excimer pulse laser with a wavelength of 308 nm and a pulse width of 28 ns. The energy density bombarding the SnSb2Te4 target is 1.5 mJ / cm 2 , the frequency is 5Hz.

[0025] Furthermore, in step (h), the film thickness is controlled by deposition time, and the deposition rate is about 0.07 nm / min.

[0026] The present invention adopts pulsed laser deposition technology to prepare SnSb2Te4 thin film with c-axis preferred orientation, and controls the surface morphology, preferred orientation, crystal quality, grain size and growth rate of the thin film by adjusting substrate temperature, deposition pressure, deposition time, laser frequency and changing substrate material. The SnSb2Te4 thin film prepared based on pulsed laser deposition technology also has the advantages of simple process, good repeatability, high crystal quality, uniform particle size and element distribution, high controllability of film thickness and morphology, and good thermoelectric performance, so it has broad application prospects in the fields of thermoelectric thin film devices and microelectronic thin film devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart of the method for preparing SnSb2Te4 thin film using pulsed laser deposition technology adopted in the present invention.

[0028] Figure 2 1 is the X-ray diffraction pattern of the SnSb2Te4 thin film prepared at different growth temperatures in Example 1.

[0029] Figure 3 X-ray diffraction patterns of SnSb2Te4 films of different thicknesses prepared on a strontium titanate substrate in Example 2.

[0030] Figure 4 This is the X-ray diffraction pattern of the SnSb2Te4 thin film prepared on the lanthanum aluminate substrate in Example 3.

[0031] Figure 5 This is a graph showing the relationship between the conductivity of the SnSb2Te4 film in Example 4 and temperature, in which the abscissa is temperature and the ordinate is conductivity.

[0032] Figure 6 This is a graph showing the relationship between the Seebeck coefficient of the SnSb2Te4 film tested in Example 4 and temperature, in which the abscissa is temperature and the ordinate is the Seebeck coefficient.

[0033] Figure 7 This is a graph showing the relationship between the power factor of the SnSb2Te4 film tested in Example 4 and temperature, in which the abscissa is temperature and the ordinate is power factor. DETAILED DESCRIPTION

[0034] The present invention is based on the demand for regulating the thermoelectric properties of SnSb2Te4 materials and the application of low-dimensional materials, protects the process conditions for preparing SnSb2Te4 thin films with preferential orientation growth using pulsed laser deposition technology, optimizes the thermoelectric properties of the film by controlling deposition parameters, and expands its application in the fields of thermoelectric thin film devices and the like.

[0035] The present invention is further described in detail below in conjunction with the examples. The following examples are only for illustration and do not limit the protection scope of the present invention in any way. Unless otherwise specified, the experimental drugs and instruments and equipment involved in the present invention can be obtained commercially.

[0036] Example 1

[0037] This embodiment provides a method for preparing a SnSb2Te4 thermoelectric thin film grown in a c-axis orientation, comprising the following steps:

[0038] (a) Preparation of target material: ① Mix Sn (99.999%), Sb (99.999%) and Te (99.999%) powders in a calculated ratio, and the molar stoichiometric ratio is Sn:Sb:Te=1:2:4; ② Place the uniformly mixed powders into a quartz tube and seal the tube in vacuum; ③ Place the vacuum-sealed quartz tube into a muffle furnace and melt sinter at 1150°C to form an ingot; ④ Crush and grind the sintered ingot into powder; ⑤ Sinter and press the obtained powder using a discharge plasma sintering technology at a sintering pressure of 50 MPa, a sintering temperature of 500°C and a sintering time of 7 min to obtain a SnSb2Te4 polycrystalline target material.

[0039] (b) Cleaning the substrate: ultrasonically cleaning the strontium titanate single crystal substrate in acetone, anhydrous ethanol and deionized water for 10 min each to remove impurities such as grease on the substrate surface.

[0040] (c) Placing the target and substrate: Place the prepared SnSb2Te4 target on the target holder in the epitaxial chamber of the pulsed laser deposition equipment; glue the cleaned substrate to the sample holder with silver glue and place it in the epitaxial chamber; adjust the distance between the SnSb2Te4 target and the strontium titanate substrate to 50 mm.

[0041] (d) Vacuuming: The back of the epitaxial chamber is vacuumed to 4×10 -4 Below Pa.

[0042] (e) Substrate heating: The strontium titanate substrate was heated at a rate of 10°C / min, and the substrate temperature was set to 250°C, 275°C, and 300°C in sequence.

[0043] (f) Adjusting the pressure: After reaching the above-mentioned vacuum degree and temperature, high-purity argon gas (99.999%) is filled in. By adjusting the valve size, the argon gas filled in and drawn out is in dynamic balance. When the balance is adjusted, the argon pressure is 0.1Pa.

[0044] (g) Thin film deposition: The substrate was blocked by a baffle, and the SnSb2Te4 target was bombarded with XeCl excimer pulse laser for surface pre-sputtering to remove impurities on the target surface. After 5 min, the baffle was removed and thin film deposition began on the single crystal substrate. The pulse laser wavelength was 308 nm, the pulse width was 28 ns, and the energy density bombarding the target was 1.5 mJ / cm 2 , the frequency is 5Hz.

[0045] (h) Cooling: After the film is deposited, it is naturally cooled to room temperature in a vacuum and then the prepared SnSb2Te4 film can be taken out.

[0046] The SnSb2Te4 thin films prepared at different temperatures (250°C, 275°C and 300°C) were subjected to X-ray diffraction tests. The experimental results are as follows: Figure 2 The angle range of the X-ray diffraction test is 20° to 80°. Figure 2 It can be seen that at the three growth temperatures, in addition to the (001) and (002) characteristic diffraction peaks of the SrTiO3 substrate, a diffraction peak in the (00l) direction of SnSb2Te4 was also detected, indicating that the prepared SnSb2Te4 film grows preferentially along the c-axis direction. As the growth temperature increases, the half-width of the diffraction peak gradually decreases.

[0047] Example 2

[0048] Using the preparation method of Example 1, SnSb2Te4 thin films were prepared on a strontium titanate (chemical formula: SrTiO3, abbreviated: STO) single crystal substrate at a deposition temperature of 300°C and a deposition time of 5 min, 10 min, and 15 min. The X-ray diffraction test results are as follows: Figure 3 As shown, in addition to the substrate peak, the (0012) and (0024) diffraction peaks of SnSb2Te4 appeared in the thin film samples of different thicknesses; the intensity of the diffraction peak became stronger with the increase of film thickness, and all had good c-axis preferred orientation.

[0049] Example 3

[0050] Using the preparation method of Example 1, SnSb2Te4 thin films were prepared on lanthanum aluminate (chemical formula: LaAlO3, abbreviated: LAO) single crystal substrates at a deposition temperature of 300°C and a deposition time of 10 minutes. The X-ray diffraction test results are as follows: Figure 4 As shown, in addition to the characteristic diffraction peaks of the LaAlO3 substrate (001) and (002), a diffraction peak in the SnSb2Te4 (001) direction was detected, indicating that the prepared SnSb2Te4 film grows preferentially along the c-axis direction.

[0051] Example 4

[0052] Thermoelectric properties of the SnSb2Te4 thin film prepared under the conditions of deposition temperature of 300°C and deposition time of 15 min in Example 2 were tested. Hall test was performed on the prepared SnSb2Te4 thin film, and the carrier concentration of the film at room temperature was measured to be 3.05×10 20 cm -3 , the mobility is 15.37cm 2 ·v -1 ·s -1 The conductivity and Seebeck coefficient of the prepared SnSb2Te4 film were tested for temperature variations, and its power factor was calculated. The test and calculation results are shown in Figure 5 , Figure 6 , Figure 7 As shown. Figure 5 It can be seen that the conductivity of SnSb2Te4 film decreases with the increase of temperature; Figure 6 It can be seen that the Seebeck coefficient of SnSb2Te4 film increases with the increase of temperature; Figure 7 It can be seen that the power factor of SnSb2Te4 film increases with the increase of temperature.

[0053] The above experimental results show that the c-axis oriented SnSb2Te4 thermoelectric film prepared by pulsed laser deposition technology in the present invention has good thermoelectric properties, is easy to integrate thermoelectric devices, and has irreplaceable advantages over bulk materials in the application of thin film devices.

Claims

1. A c A method for preparing an axially oriented SnSb2Te4 thermoelectric film, characterized in that: The steps include: (a) Preparation of target material: ① Mix Sn, Sb and Te powders in a molar ratio of Sn:Sb:Te=1:2:4; ② Put the powders mixed in step ① into a quartz tube, and then seal the tube in vacuum; ③ Put the vacuum-sealed quartz tube into a muffle furnace for melting and sintering to form an ingot; ④ Crush and grind the sintered ingot into powder; ⑤ Sinter and press the powder obtained in step ④ using a spark plasma sintering technology to obtain a SnSb2Te4 target material; (b) cleaning the substrate: using an ultrasonic cleaning method to remove impurities on the surface of the substrate; the substrate is strontium titanate; (c) Placing the target: placing the SnSb2Te4 target obtained in step (a) on the target holder of the epitaxial chamber of the pulsed laser deposition equipment; (d) Placing the substrate: The cleaned substrate is glued to the center of the sample holder with silver glue and sent to the heating stage of the epitaxial chamber of the pulsed laser deposition equipment; the distance between the SnSb2Te4 target and the substrate is 50 mm; (e) Vacuuming: The back vacuum of the epitaxial chamber of the pulsed laser deposition equipment is evacuated to less than or equal to 4×10 -4 Pa; (f) Substrate heating: Run the heating program to heat the substrate at a rate of 10 °C / min until the substrate temperature rises to 250 °C~300 °C; (g) Adjusting the pressure: After the substrate temperature reaches the set temperature, high-purity argon gas is filled into the epitaxial chamber of the pulsed laser deposition equipment, and the size of the filling and exhaust valves is adjusted to keep the dynamic equilibrium pressure of the argon gas at the set pressure; (h) Deposition of thin film: The SnSb2Te4 target material was bombarded with a pulsed laser to perform surface pre-sputtering, and after the pre-sputtering, a SnSb2Te4 thin film was deposited on the substrate; the deposition time was 5 min, 10 min or 15 min; (i) Cooling: After sputtering, the material is naturally cooled to room temperature in a vacuum; (j) Taking samples: After filling the epitaxial chamber of the pulsed laser deposition equipment with gas, taking out the obtained SnSb2Te4 thin film sample; In step (g), the argon pressure in dynamic equilibrium is 0.1 Pa; In step (h), the pulse laser is a XeCl excimer pulse laser with a wavelength of 308 nm and a pulse width of 28 ns; the energy density bombarding the SnSb2Te4 target is 1.5 mJ / cm 2 , with a frequency of 5 Hz.

2. according to claim 1 c A method for preparing an axially oriented SnSb2Te4 thermoelectric film, characterized in that: In step (a) of step ③, the sintering temperature of the powder in the muffle furnace is set to 1150°C.

3. According to claim 1 c A method for preparing an axially oriented SnSb2Te4 thermoelectric film, characterized in that: In step ⑤ of step (a), during the spark plasma sintering process, the powder is sintered at a pressure of 50 MPa, a temperature of 500°C, and a sintering time of 7 min.

4. according to claim 1 c A method for preparing an axially oriented SnSb2Te4 thermoelectric film, characterized in that: In step (b), the substrate is cleaned by placing the substrate in acetone, anhydrous ethanol and deionized water in sequence and ultrasonically cleaning them for 10 minutes respectively.

5. Prepared by the method according to any one of claims 1 to 4 c Axially oriented grown SnSb2Te4 thermoelectric thin films.

Citation Information

Patent Citations

  • Optical information recording medium

    JP1992134642A

  • Thermoelectric thin film nanocomposites

    KR1020180057798A